The Portrayal of Interpersonal Violence in Malaysian Independent Online Media - Saifuddin AVA, Norizzati; Zanuddin, Hasmah (International Journal of Psychosocial Rehabilitation, 2020)
Malaysians have been shocked by the trending cases of interpersonal violence that happened in Malaysia. This interpersonal violence may involve and commit to a person or family members whom they have a relationship with. Five components of interpersonal violence are comprised of youth violence, child maltreatment, intimate violence, elder abuse, and sexual violence. Unfortunately, it is difficult to make Malaysian society aware of these risks and dangers that may influence the way people behave and act towards each other. From a media perspective, attention to the issue declined when journalists and editors moved on from this reporting this issue. There is a need to supply more information regarding these behaviours to generate attention on this issue. The purpose of conducting a study on this issue is to determine the way Malaysian independent online media portray interpersonal violence cases. The objectives of this study are to study the media agenda, public agenda, and policy agenda used in interpersonal violence reporting in Malaysian independent online news. This study used quantitative content analysis by analysing 140 news articles from two selected independent online news sources as the sample of this study. Two independent online news sites were used in this study, which include Malaysiakini.com and Free Malaysia Today.com. From this study, media plays an important role as the agenda setter in addressing the criticality of interpersonal violence issues to Malaysian society. The portrayal of interpersonal violence news is important to shape the pattern of Malaysians in viewing the seriousness of this matter. This result can be used to plan strategies by increasing public knowledge on the criticality of interpersonal violence so that the public aware of the issue.